Histomorphological changes in gall bladder diseases and its association with helicobacter infection - K.C., Geetika; Talwar, OP (Journal of Pathology of Nepal, 2014)
Background: Gall bladder diseases can be an incidental finding and when symptomatic, present with signs and symptom of cholecystitis and cholelithiasis. On histopathological examination however wide range of pathological changes are encountered including carcinoma. Several studies have been carried out to establish relationship of helicobacter infection with gallbladder diseases. This study tries to look at the frequency of risk factors, spectrum of histological changes and the relationship between different types of gallbladder diseases and helicobacter infection. Materials and Methods: Total of 500 gallbladder specimen received over the period of 24 months was included in the study. Bile culture and histopathological examination cholecystectomy were performed with routine hematoxylin and eosin stain and Giemsa stain. Results: Out of the 500 cases. Helicobacter was seen in 166(33%) of cases. Carcinoma was seen in 7 (1%) cases. Helcobacter infection was seen positive in 5/7 (71%) malignant cases which showed a statistically significant p value of 0.03. Conclusion: Cholecystitis is the most common gallbladder disease. All gallbladder carcinomas were incidental finding and were of lower grade and stage. Helicobacter infection was prevalent in variety of gallbladder pathology and had significant association with gallbladder carcinoma. However, definite relation between the helicobacter infection and gallbladder diseases cannot be concluded. <!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> DOI: http://dx.doi.org/10.3126/jpn.v4i8.11607 Journal of Pathology of Nepal; Vol.4,No.8 (2014) 617-622